PENGARUH MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT FEDERAL INTERNATIONAL FINANCE CABANG SUNTER JAKARTA UTARA - Floryani Natalin Yuantri; Darmadi Darmadi (CV. Denasya Smart Publisher, 2025)
This study aims to determine the effect of motivation and physical work environment on employee performance at PT Federal international finance sunter branch, north Jakarta. This research uses quantitative methods. Where the sampling technique uses saturated samples because the population totals 83 employees. Technical analysis and data testing include, validity and reliability tests, classical assumption tests, simple and multiple linear regressions, correlation coefficient tests, determination coefficient tests, and hypothesis testing. Based on the results of the first hypothesis test, namely the effect of motivation on employee performance, the tcount > ttable value is obtained (16.494> 1.989) with a significance value of 0.000 < 0,05. <0.05. So it can be stated that partially motivation has a positive and significant effect on employee performance at PT Federal International Finance Sunter Branch, North Jakarta. While testing the second hypothesis, namely the effect of the Physical Work Environment on employee performance at PT Federal International Finance, Sunter Branch, North Jakarta, obtained a tcount>So it can be stated that partially motivation has a positive and significant effect on employee performance at PT Federal international finance sunter branch, north Jakarta. While testing the second hypothesis, namely the effect of the Physical Work Environment on employee performance at PT Federal International Finance, Sunter Branch, North Jakarta, obtained a tcount> ttable value (16,494> 1,989) with a significance value of 0.000 Ftable (229,404 > 3.96) with a significance value of 0.000 < 0,05, meaning that simultaneously Motivation and Physical Work Environment have a significant effect on employee performance at PT Federal International Finance, Sunter Branch, North Jakarta